Big bad wool - Swann, Leonie, 1975- (Swann, Leonie, 1975- Sheep detective stories, 2025)
"In the highly anticipated follow-up to the breakout offbeat hit Three Bags Full, an enterprising flock of sheep must get to the bottom of just who-or what-is leaving a trail of grisly destruction in its wake. With one solved mystery under their wooly belts, the time has come for the sheep of Glennkill to explore Europe. Together with their new shepherdess, Rebecca, they move into their winter quarters in the shadow of a French chateau. But their new home is far from idyllic. A number of the sheep from the previous flock have disappeared, and deer are dying an unnatural death in the forest. The goats from the neighboring pasture have a theory: a werewolf. Could that be real, or just a fantasy? When a human falls victim, it becomes clear that even fantasies can be fatal. And the last thing the sheep want is to lose another shepherd. With the help of the strange goats in the neighboring field, they follow the werewolf's trail in a desperate attempt to save both themselves and Rebecca with sheep logic, courage, and concentrated food"--